Analysing significance of key quality factors for management of construction projects - Žanesa Ljevo; Mladen Vukomanović; Nerman Rustempašić (Građevinar, 2017)
The study of key quality factors relating to construction project processes in Bosnia and Herzegovina and Croatia has revealed that these factors are not accepted similarly by investors, contractors/subcontractors and project managers/consultants/designers. The first four ranked factors are: coordination of participants, communication, expertise/knowledge, and planning and control, with various priorities among the mentioned participants. The study has also revealed that the significance of individual quality factors differs during various phases of construction projects depending on differing management standpoints.